2024
DOI: 10.1161/hypertensionaha.122.19940
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease: Early-Life Antecedents and Long-Term Implications for the Brain, Aging, Stroke, and Dementia

Ellen V. Backhouse,
James P. Boardman,
Joanna M. Wardlaw

Abstract: Cerebral small vessel disease is common in older adults and increases the risk of stroke, cognitive impairment, and dementia. While often attributed to midlife vascular risk factors such as hypertension, factors from earlier in life may contribute to later small vessel disease risk. In this review, we summarize current evidence for early-life effects on small vessel disease, stroke and dementia focusing on prenatal nutrition, and cognitive ability, education, and socioeconomic status in childhood. We discuss p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…The totality of an individual's old infarct burden, including covert or silent brain infarcts, may influence VCI, 17 but study interpretation may be limited by lack of lesion subtyping (eg, small subcortical versus cortical), terminology, CI subtyping (eg, vascular versus Alzheimer), or accounting for premorbid cognitive ability, which increases the risk of stroke, 22 PSCI/PSD, 23 and SVD. 24 Studies in community-dwelling populations have shown that lacunes associate with worse cognitive function, 25 silent thalamic infarcts associate with longitudinal decline in memory performance, 26 and incident subcortical infarcts convey the highest risk of incident dementia versus other incident infarct subtypes or no infarcts. 27 In communitydwelling older adults without stroke or dementia, in whom covert infarcts occur in up to one-fifth, 26,28 there is a trend between all-cause incident dementia and the presence of any MRI-defined covert or, silent, brain infarct.…”
Section: Infarctsmentioning
confidence: 99%
See 1 more Smart Citation
“…The totality of an individual's old infarct burden, including covert or silent brain infarcts, may influence VCI, 17 but study interpretation may be limited by lack of lesion subtyping (eg, small subcortical versus cortical), terminology, CI subtyping (eg, vascular versus Alzheimer), or accounting for premorbid cognitive ability, which increases the risk of stroke, 22 PSCI/PSD, 23 and SVD. 24 Studies in community-dwelling populations have shown that lacunes associate with worse cognitive function, 25 silent thalamic infarcts associate with longitudinal decline in memory performance, 26 and incident subcortical infarcts convey the highest risk of incident dementia versus other incident infarct subtypes or no infarcts. 27 In communitydwelling older adults without stroke or dementia, in whom covert infarcts occur in up to one-fifth, 26,28 there is a trend between all-cause incident dementia and the presence of any MRI-defined covert or, silent, brain infarct.…”
Section: Infarctsmentioning
confidence: 99%
“…Studies should account for followup duration 35 and premorbid cognitive ability. 24 Current VCI criteria refer to extensive and confluent WMH but are mostly based on smaller, older studies 36 when MRI was less sensitive, risk factor management was different, and early life factors were not considered. 24 A large-scale reevaluation of the role of nonconfluent, focal or mild-moderate WMH, specific WMH tracts, and WMH regression 34…”
Section: Cortical Microinfarctsmentioning
confidence: 99%
“…Various cardiovascular and metabolic disorders are linked with vascular inflammation, including diabetes, obesity, hypercholesterolemia, senescence, and aging, which have already been well discussed in recent publications. [30][31][32][33][34][35] In this article, we provide a current overview and concepts about inflammatory mechanisms and epigenetic modifications in the vasculature and their contribution to vascular injury associated to hypertension and neurodegenerative diseases. Finally, we synthesize current evidence to demonstrate how these pathways may represent novel therapeutic targets, offering promising avenues for the treatment of vascular disorders.…”
mentioning
confidence: 99%